State and Problems Encountered by Postal Service Providers in The Republic of Bulgaria - Zhelyazkova, Donka; Stojanov, Michal (Research Papers, 2023)
Digital transformation, the migration of product exchange to an online environment and the uncertainty of the economic system are forming new challenges for operators providing postal and logistics services. Their key role in the exchange economy brings to the fore the problems of the level and complexity of the service offered. In the present work, the current dimensions of the offer of postal services in Bulgaria are investigated, which allows to locate main problems and their possible solutions, which are defined in the dimensions of innovative adaptation of the achievements of scientific progress, investments in new equipment and technologies and provision of business information security.
Keywords: Digitization; Labor productivity; Revenues; Postal services; Postal operator